Pengaruh Model Pembelajaran Means Ends Analysis (MEA) Terhadap Hasil Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas VIII SMP Negeri 4 Laguboti - Sipayung, Nelfide Christiani; Samosir, Taripar Aripin; Nababan, Andrianus (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2023)
The aim of this research is to determine the learning outcomes of students' Christian Religious Education and Character Education which are taught using the Means Ends Analysis (MEA) learning model which are higher than those taught using the conventional learning model in class VIII of SMP Negeri 4 Laguboti. This research uses a Posttest-Only Control type experimental method. The population is the entire class VIII of SMP Negeri 4 Laguboti, totaling 190 people. The sample was determined using a technique taken deliberately (purposive sampling) with the specified conditions that the learning material being experimented with was in that class, namely 31 students in class VIII-C as the experimental class and 31 students in VIII-E as the control class. The research instrument uses a 30-item test. The test used is the Separated Variance t test according to the analysis requirements, namely n-nz and the variance of the two sample groups is homogeneous. The results of hypothesis testing obtained a tcount value of -9.5>ttable (α=0.05, dk-n1+n2 2-60) = ttable 1.671, so H0 was rejected and H1 was accepted. This research concludes that the learning outcomes of Christian Religious Education and Character for students taught using the Means Ends Analysis (MEA) learning model are higher than those taught using the conventional learning model in class VIII of SMP Negeri 4 Laguboti.